Leiobracon, a new genus of the subfamily Braconinae (Hymenoptera, Braconidae) from Vietnam - Dzuong, Nguyen Van; Long, Khuat Dang; Achterberg, Cornelis Van; Hiep, Nguyen Duc (Zootaxa, 2024)
The genus Leiobracon gen. nov. and the type species Leiobracon vietnamicus sp. nov., are described from Vietnam. The new genus differs morphologically from all known braconine genera with bifurcate tarsal claws (Mesobracon group of genera) by having the metasoma smooth, the first metasomal tergite more than 2.6 × longer than wide medially, with its lateral areas largely reduced and without crenulations.